From Inter-Religious Dialogue to Intra-Religious Dialogue: An Original Perspective of André Scrima’s Thought - Mihai-Iulian Danca (Religions, 2023)
André Scrima was confronted from the very beginning with the multifaceted reality of the religious phenomenon. To help us understand this reality, his theological approach can be compared to that of the reverse perspective in Byzantine art: the further away an object is, the larger it becomes, and the closer it is, the smaller it becomes. From this perspective, the usual landmarks of knowledge are reversed, since it is the viewer who decides on the validity and truth of knowledge, and not the objective reality that would force adherence without any right to object. In theological terms, we could say that the ultimate significance of religious pluralism is not its outward manifestation nor the objectivity of its material data. In the final analysis, the person of faith brings their own experience into play as they decide on the truth of religions in general. The vanishing line no longer lies in the phenomenal exteriority of data but within each one. We will call this perspective intra-religious dialogue because, in addition to starting from the inner dimension of the experience of faith, it allows each of these experiences to reflect the “seeds of truth” that the Spirit scatters where it wills.